ANALISIS ALUR PEMASARAN IKAN TUNA MADIDIHANG DI PASAR ARUMBAE KOTA AMBON - Ruslan Husen Saban Tawari; Jacobus B. Paillin; Iqno Tikno; Salma Salma; Friesland Tuapetel (Universitas Pattimura, 2024)
Arumbai Market, Ambon, Maluku Province is a central market for fishery sales that has a great opportunity in the transaction of fishery products, both from inside and outside the island of Ambon. One type of fish that is excellent in the marketing of fishery products is Tuna. The purpose of this study is to analyze the feasibility of catching and distributing yellowfin tuna caught in Tuna fish marketed in the Arumbai Ambon market. The data collection method used primary data sources and secondary data sources. Based on the results of the measurement of length and weight of the type of Yellowfin tuna marketed in the Arumbai Ambon market, it is dominated by the length 21 – 98.1 cm Fl and the weight 0.1-15 kg amounting to 545 individuals while in the length 98.2 – 115.2 cm Fl and the weight 15.2-20 kg amounting to 55 individuals, while the percentage of the length of Yellowfin tuna marketed in the Arumbai Ambon market based on the location of its supply shows that the supply of AFP is 7.50% of fish that are worth catching and 36.67% of fish are not worth catching. The percentage of fish supply contribution that is not worth catching to the Arumbai Ambon Market in order is the Latuhalat Village supply of 23.83% is not worth catching 0.50% is worth catching, the Huamual Belakang supply of 26.50% is not worth catching 0.83% is worth catching, and from the Company of 3.83% is not worth catching 0.33% is worth catching.